Pengaruh Kompetensi Kepribadian terhadap Kualitas Kehidupan Kerja Guru di SMA Man Ana Pamijahan Bogor - Zatiyah; Hana Lestari; Ima Rahmawati (Jurnal Sains Indonesia, 2020)
Personality competencies affect the quality of teacher's work life. This study aims to determine the effect of teacher personality competencies on the quality of work life. The correlational method used in this study involved 35 subjects from Man Ana High School teachers. The instruments used were personality competency questionnaires and the quality of work life of teachers using a Likert scale (1-5). The results of this study indicate that (1) there is a relationship between personality competence (X) on the quality of work life of teachers (Y) of 0.309 and included in the low category; (2) there is a positive but not significant effect between personality competence (X) on the quality of work life of teachers (Y), with a regression model Ŷ = 61.637 + 0.125 (X); (3) personality competence contributes a little that is 9.5%, while the rest is influenced by other variables not examined.